Hydro-Electrometallurgical Extraction Of Zinc From Zinc Bearing Wastes - Anwar, Muhammad Harith Irfan Khairul (Universiti Sains Malaysia, 2017)
Galvanizing, which is one of the coating techniques nowadays also produces wastes like all metallurgical process. Extracting the zinc back from the galvanizing zinc wastes is essential with the implementation of strict environmental protection regulations as well as to reduce the negative effects to the environment. The galvanizing zinc wastes used in this research consist of 64.80 wt% of zinc oxide occurring with other minerals of different wt%. Prior to leaching of the galvanizing zinc wastes, the sample was roasted at 400˚C and undergone hot-water leaching. The sample was then leached at varying temperatures (50,70 and 90˚C), concentration of H2SO4 (0.9, 1.8 and 3.6 M) and at time (1,2 and 4 hours). In 2 hrs leaching time, at 70˚C, about 90.10% of zinc recovery was achieved when leaching was conducted in 1.8 M sulfuric acid. While at the same leaching temperature and concentration of H2SO4 and at longer leaching time (4hrs), about 98.58% of zinc was recovered. However, when leaching was carried out at 70˚C with 3.6 M concentration of sulfuric acid conducted in 2 hrs, about 99.53% of zinc recovered. The pregnant leach solution was then purified by iron precipitation and copper cementation followed with electrowinning procedure. The electrowinning process was carried out in a 50mL beaker using lead anode and aluminium cathode with electrode distance was set to 12 cm to obtain high current efficiency with low energy requirement. At the optimum condition of electrowinning, zinc metal with a flake like structure was observed deposited at the aluminium cathode with a current efficiency between the range 93.9% and 98.5%. The electric energy requirement for the electrowinning process is in the range of 2.66 to 2.79 kWh/kg.